Evaluasi Sistem Pengendalian Intern dalam Meminimalkan Resiko Kredit Macet di Koperasi Prima Agung Sejahtera Surabaya - Ningsih, Ajeng Kusuma; Kusumaningtyas, Menur (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
A mechanism is needed to control the problem of bad claims that often occurs in financial institutions. This study aims to measure the extent to which internal credit controls contribute to the reduction of bad claims. A descriptive qualitative research approach was used. Although there are still some limitations, this study shows that the implementation of internal controls in the credit system can help improve credit quality and reduce the percentage of bad claims.